Influence of hospital admission in the pharmacotherapy complexity of HIV+ patients - María de las Aguas Robustillo Cortés; Ramón Morillo Verdugo; Esther María Barreiro Fernández; Ascensión Pavón Plata; Patricia Monje Agudo (Farmacia Hospitalaria)
Objective: To determine the variation in the pharmacotherapy complexity index in HIV+ patients after hospital admission. Method: A retrospective, single-center study with HIV+ patients on antiretroviral treatment (ART) who were admitted to hospital between 2008 and 2015 were conducted. Demographic, analytical, clinical and pharmacotherapy variables were collected, as well as those about the use of healthcare resources. The primary endpoint was the variation in the overall complexity index after a hospital admission, measured through the MRCI tool (University of Colorado). There was also an analysis of the variation in adherence to ART, and of the causes that led to an increase in pharmacotherapy complexity after hospitalization. Results: The study included 146 patients (84.9% male) with 45.3 ± 9.1 years as mean age; 30.8% of these patients had experienced an admission to hospital in the previous year, with a median stay of seven days (IQR: 4-12,5). The mean overall complexity before hospital admission was 14.5 ± 7.2 vs. 16.5 ± 8.0 after admission, with a significant difference (1.97 [CI = 0.85;3.09]). The percentage of patients adherent to ART before admission was 58.3% vs. 41.8% after admission (p = 0.023). The only factor associated to an increase in complexity was having five or more chronic drugs prescribed before admission (OR = 3.146 [1.045-9.471]). Conclusion: The overall pharmacotherapy complexity increased after hospital admission, reducing the adherence to ART. Chronic treatment prescribed before admission was the only factor associated with an increase in complexity after admission